The Existence of Elopement in Perspective Value Education (Study of Penomenology in the Context of Marriage of the Bima Society) - Suharyanto H. Soro (Budapest International Research and Critics University, 2021)
This study aims to find educational values in the procession of elopement. The term of elepement refers to an activity consciously carried out by two people (a man and a woman) to make an agreement to become a legal husband and wife. Meanwhile, value education in this context refers to the attributes that characterize the behavior of the activity. Researchers used a qualitative approach with the method of observation and interviews. The observation method was non-participant, while the interview was conducted in depth. The selection of respondents as the object of the interview was carried out in a purposeful manner. The data obtained from the use of the two methods were used as valid data for in-depth analysis to give new findings or new theories. The findings of this study indicated that the elopement activity carried out by male and female couples has become the culture of the local community to lead to a legal husband and wife. This accompaniment activity is only carried out by couples who have a low level of education. In other words, contraband rarely or even does not occur in highly educated (bachelor) couples. Education contributes positively to awareness and prevents these stragglers from acting as shortcuts or imposing their will because the woman's parents do not agree with her daughter's husband-to-be.